Superelectrophilic Behavior of an Anion Demonstrated by the Spontaneous Binding of Noble Gases to [B12Cl11]−. Issue 27 (31st May 2017) - Rohdenburg, Markus; Mayer, Martin; Grellmann, Max; Jenne, Carsten; Borrmann, Tobias; Kleemiss, Florian; Azov, Vladimir A.; Asmis, Knut R.; Grabowsky, Simon; Warneke, Jonas
Abstract: It is common and chemically intuitive to assign cations electrophilic and anions nucleophilic reactivity, respectively. Herein, we demonstrate a striking violation of this concept: The anion [B12 Cl11 ] − spontaneously binds to the noble gases (Ngs) xenon and krypton at room temperature in a reaction that is typical of "superelectrophilic" dications. [B12 Cl11 Ng] − adducts, with Ng binding energies of 80 to 100 kJ mol −1, contain B−Ng bonds with a substantial degree of covalent interaction. The electrophilic nature of the [B12 Cl11 ] − anion is confirmed spectroscopically by the observation of a blue shift of the CO stretching mode in the IR spectrum of [B12 Cl11 CO] − and theoretically by investigation of its electronic structure. The orientation of the electric field at the reactive site of [B12 Cl11 ] − results in an energy barrier for the approach of polar molecules and facilitates the formation of Ng adducts that are not detected with reactive cations such as [C6 H5 ] + . This introduces the new chemical concept of "dipole‐discriminating electrophilic anions." Abstract : Unexpected reactivity : The binding of the noble gases Xe and Kr to the anion [B12 Cl11 ] − is explained with the exceptional properties of the electric field in the vicinity of the undercoordinated boron atom. Whereas polar nucleophiles such as water face a barrier, neutral unpolar species such as N2 or noble gases are preferred, rendering [B12 Cl11 ] − a "dipole‐discriminating electrophilic anion".